Rogalsky Effect in the Indonesian Stock Exchange (an Event Study on the Manufacturing Sector in 2024) - Yogo Heru Prayitno; Niki Hadian; Yoga Tantular Rachman (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study is classified as an event study. The researcher observed whether the Rogalsky Effect phenomenon occurred on the Indonesian Stock Exchange, particularly in the manufacturing sector. This study examined whether there were abnormal returns before and after the event and whether there were abnormal returns in each event period. The researcher used 200 periods for the estimation period and 27 periods before and 27 periods after the event. The research sample used 57 companies from 228 companies listed in the manufacturing sector on the Indonesia Stock Exchange in 2024. Paired Sample T-test and One Sample T-test were used to test the hypothesis. The results showed that there was no difference in stock returns on Mondays in January compared to returns on Mondays in non-January months for manufacturing sector companies, and there were abnormal returns in 19 event periods. This indicates that an abnormal return occurred during this period due to market reaction to the information that emerged at that time. The occurrence of abnormal returns in this period reflects changes in investor expectations regarding stock prices in response to new information perceived as valuable. the tests conducted, it can be concluded that a seasonal anomaly in the form of the Rogalsky Effect occurs in the Indonesian Stock Exchange, particularly in the manufacturing sector.